Application of a strong FSI coupling scheme for the numerical simulation of bileaflet mechanical heart valve dynamics: study of wall shear stress on the valve leaflets. (26th June 2012) - Annerel, Sebastiaan; Degroote, Joris; Vierendeels, Jan; Claessens, Tom; Ransbeeck, Peter Van; Dahl, Sigrid K.; Skallerud, BjÁ?rn; Hellevik, Leif Rune; Segers, Patrick; Verdonck, Pascal
One of the major challenges in the design of Bileaflet Mechanical Heart Valves (BMHVs) is reduction of the blood damage generated by non–physiological blood flow. Numerical simulations provide relevant insights into the (fluid) dynamics of the BMHV and are used for design optimisation. In this paper, a strong coupling algorithm for the partitioned Fluid–Structure Interaction (FSI) simulation of a BMHV is presented. The convergence of the coupling iterations between the flow solver and the leaflet motion solver is accelerated by using a numerically calculated Jacobian with the derivatives of the pressure and viscous moments acting on the leaflets with respect to the leaflet accelerations. The developed algorithm is used to simulate the dynamics of a 3D BMHV in three different geometries, allowing an analysis of the solution process. Moreover, the leaflet kinematics and the general flow field are discussed, with special focus on the shear stresses on the valve leaflets.